2011
DOI: 10.1111/j.1755-0998.2011.02999.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene discovery in the Antarctic fur seal (Arctocephalus gazella) skin transcriptome

Abstract: Next-generation sequencing provides a powerful new approach for developing functional genomic tools for nonmodel species, helping to narrow the gap between studies of model organisms and those of natural populations. Consequently, massively parallel 454 sequencing was used to characterize a normalized cDNA library derived from skin biopsy samples of twelve Antarctic fur seal (Arctocephalus gazella) individuals. Over 412 Mb of sequence data were generated, comprising 1.4 million reads of average length 286 bp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…Furthermore, species differentiation of crow species Corvus corone and Corvus cornix was detected through differences in their gene expression profiles, whereas the use of several DNA markers failed to detect this differentiation [18]. In mammals, transcriptome analyses in the Antarctic fur seal Arctocephalus gazella using mRNA derived from skin tissues detected several thousand putative microsatellite loci and SNPs [19]. These pioneering studies have suggested that NGS provides a massive amount of useful information for population genetics in non-model organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, species differentiation of crow species Corvus corone and Corvus cornix was detected through differences in their gene expression profiles, whereas the use of several DNA markers failed to detect this differentiation [18]. In mammals, transcriptome analyses in the Antarctic fur seal Arctocephalus gazella using mRNA derived from skin tissues detected several thousand putative microsatellite loci and SNPs [19]. These pioneering studies have suggested that NGS provides a massive amount of useful information for population genetics in non-model organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Just such an opportunity is provided by a large body of 454 sequence data recently generated for the Antarctic fur seal, Arctocephalus gazella [15]. A long-term genetic study of this colonially breeding polygynous pinniped species at Bird Island, South Georgia [16] has identified remarkably consistent relationships between heterozygosity measured at 9–76 microsatellite loci and a variety of important fitness traits, from male reproductive success through body size to attractiveness [17][20].…”
Section: Introductionmentioning
confidence: 99%
“…This was constructed using 454 sequence reads generated from two different cDNA libraries, one comprising skin samples from 12 individuals [33] and the other comprising necropsy samples from nine individuals [34]. Assembly of these data using NEWBLER generated a total of 23,096 contigs [34], which we refer to as the ‘454 transcriptome’.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the extent of overlap between SNPs called by different methods, we revisited two sets of SNPs called from the 454 transcriptome using NEWBLER and SWAP454 respectively [33, 34]. A small number of SNPs within these datasets were duplicated or had an alternative allele frequency of one.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation